De novo metagenomic assembly of microbial communities from the lower convective layer of the Red Sea Atlantis II brine environment. - Ali, Osama Said (AUC Knowledge Fountain, 2013)
The lower convective layer of the Red Sea Atlantis II brine pool (ATII-LCL) is an unexplored environment that is characterized by harsh conditions of high temperature (68ºC), high salinity (26%), high concentration of heavy metals and very low oxygen content. Microbial communities inhabiting this extreme environment are expected to have unique structural and functional adaptations to survive such harsh conditions. These adaptations can be expressed by novel genes or new metabolic pathways. The recent advances in the next generation sequencing technologies have increased the size of the generated reads (500 bps in 454 pyrosequencing) and lowered the sequencing cost per gigabase. As a result, research efforts became more feasible to reveal the mystery of such an interesting environment and to discover novel proteins that might have a useful biotechnological application. This study is the first attempt to establish a metagenomic assembled dataset of the environmental sample taken from the ATII-LCL. Three successive runs of 454 random shotgun sequencing were performed producing a large size dataset of 1.5 Gbs and 4.4 million reads. This approach has been used to increase the sequence coverage of metagenomic datasets in order to overcome the high diversity of some microbial communities. De novo assembly of the pooled reads from all sequencing runs resulted in a 40,693 contigs with maximum contig size of 350 kb. The comparison of different assembly versions of individual runs showed that we have not yet reached a complete coverage of the genomes contained in the metagenomic sample. Also, this metagenomic dataset has shown a high complexity concerning the community structure due to the absence of a dominant taxonomic classification. The taxonomic classification of the assembled dataset has been distributed between three major bacterial orders, Burkholderiales, Rhizobiales and Pseudomonadales and one Archaeal class Euryarchaeota. The newly established dataset has been used to annotate an operon for mercury resistance genes. The annotated Mercuric reductase gene (MerA) has been synthesized and expressed in the lab showing a high enzyme activity compared to its terrestrial peers.